Management of the Airway in Apert Syndrome. Issue 1 (January 2016) - Xie, Carol; De, Sujata; Selby, Andrew
Abstract : Abstract: The management of the airway in Apert syndrome is complex and multidisciplinary. This rare syndrome, occurring in up to approximately 1 in 65, 000 live births, results in airway compromise at various anatomic levels, in addition to abnormal central respiratory drive. Obstructive apneas arise because of decreased airway caliber, which may occur in the form of congenital bony nasal stenosis, choanal atresia, a deviated nasal septum, a narrowed nasopharynx, a thick long soft palate, lateral palatal swellings, and a tracheal cartilage sleeve. Central apneas in Apert syndrome arise because of raised intracranial pressure and/or Chiari malformations. The purpose of this study was to investigate our treatment methods and outcomes in optimizing the airway in this complex, rare and interesting cohort of patients who present with airway compromise. Patients with Apert syndrome were retrospectively evaluated during a period from 1990 to 2013. Treatments for obstructive apnea were dilatation of nasal airways and choanal atresia repair, adenoidectomy, tonsillectomy, early midface advancement, and noninvasive ventilation. The insertion of ventriculoperitoneal shunts, fronto-orbital advancement, and Chiari decompression aid in managing central apneas. The authors present our experience at Alder Hey Children's Hospital, Liverpool, one of the 4 Supraregional Craniofacial Units in the United Kingdom.